Modern technique for pest control in organic plant production - Luka Šumanovac; Mladen Jurišić; Petar Lukač; Stjepan Sito; Domagoj Zimmer (Glasnik Zaštite Bilja, 2022)
Sažetak The paper presents modern agricultural techniques in plant protection through thermal protection, the use of vacuum systems, the mechanical application of brush cultivators and various weeds and the use of modern robots. The use of these methods enables the control of pests in an ecological way, which is increasingly necessary in everyday plant production. The paper will provide explanations and principles of work with which it is possible to effectively and relatively quickly control pests. The use of the above enables completely organic plant production without negative consequences for the end user